PENGARUH KUALITAS PRODUK, HARGA, PROMOSI, DAN ETNOSENTRISME KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN PRODUK KOSMETIK BUATAN DALAM NEGERI (STUDI KASUS DI KOTA PONTIANAK) - B11110107, LUSIANA (Jurnal Manajemen Update, 2014)
In accordance to the economic growth, technology and culture in the modern era, has become a necessity beauty treatments that are considered important for some people, especially for women. Specifically this study to create a conceptual framework with the variable quality of product (X1), price (X2), promotion (X3), and consumer ethnocentrism (X4) and domestic cosmetics purchase decision (Y) aims to analyze whether or not the effect of product quality, price, promotion, and consumer ethnocentrism on purchasing decisions domestic cosmetics in Pontianak. The research data was obtained from questionnaires were taken using purposive sampling method sampling technique in which researchers have made a lattice / certain criteria based on the characteristics that will be the subject of the study sample (Sugiyono, 2004: 73). With a sample size of 100 respondents (net accumulation of damaged and missing questionnaires). Using quantitative analysis processed with SPSS 16 include the validity and reliability, the classic assumption test (test for normality, linearity test, test heteroscedasticity, and multicollinearity test), multiple regression analysis, t test and F test results of this study indicate that all the independent variables simultaneously or partially significantly influence purchasing decisions domestic cosmetics in Pontianak. Keywords: Quality of product, price, promotion, consumer ethnocentrism and purchase decision.